Knowledge and perceptions of patients with hypertension on adverse drug reation reporting in the community of Dikgale, Mamabolo, Molepo and Mothapo health and demographic surveillance site - Molepo, Molatela Rose (My University, 2025)
Introduction: Both adverse drug reactions and hypertension pose a threat to global public health. Underreporting of adverse drug reactions (ADRs) by patients and healthcare professionals is still a major challenge to effective pharmacovigilance system globally. Underreporting of ADRs by patients is particularly low in Africa because of lack of knowledge and awareness. In South Africa, there are platforms for patients and healthcare professionals to report ADRs, but inadequate knowledge and awareness continue to hinder the progress of effective ADR reporting. Most patients report to healthcare professionals. Purpose: To assess the knowledge, perceptions and experiences of ADR reporting among patients on anti-hypertensives attending primary health care (PHC) facilities under the Dikgale, Mamamolo, Mothapo and Molepo Health and Demographic Surveillance Site (DIMAMO HDSS), Limpopo Province, South Africa. Methodology: This was a quantitative cross-sectional study. A questionnaire was used to collect data from 384 respondents. Data was collected from six PHC facilities under the DIMAMO HDSS. The data was analysed using the Statistical Package for Social Sciences version 29 and Microsoft Excel. Results: Majority of the respondents were female, unemployed and aged 61 years and above. The common antihypertensive medications were amlodipine, enalapril and hydrochlorothiazide with most reported side effects experienced from enalapril. The term medication side effect was more common than ADRs. There was an overall lack of knowledge among respondents with only two respondents familiar with the word ADR. The perspective was positive in that patients identified themselves as responsible for detection and reporting of ADRs. Lack of knowledge and unemployment served as barriers for ADR reporting Conclusion: The population of DIMAMO generally had lack of knowledge on side effects and ADRs. Medication side effect was a more common term to the respondents than ADR. Only a few respondents reported to have had experienced an ADR or a side effect. The respondents had a positive perspective on reporting ADRs despite having limited knowledge.
Thesis (M. Pharm. (Pharmacology)) -- University of Limpopo, 2025
Keywords: Adverse drug reactions; Knowledge; Medication side effects; Public health surveillance; Drugs -- Side effects; Hypertension; Pharmacoepidemiology; Drug monitoring